2022
DOI: 10.1073/pnas.2212642119
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous microdroplets enable abiotic synthesis and chain extension of unique peptide isomers from free amino acids

Abstract: Amide bond formation, the essential condensation reaction underlying peptide synthesis, is hindered in aqueous systems by the thermodynamic constraints associated with dehydration. This represents a key difficulty for the widely held view that prebiotic chemical evolution leading to the formation of the first biomolecules occurred in an oceanic environment. Recent evidence for the acceleration of chemical reactions at droplet interfaces led us to explore aqueous amino acid droplet chemistry. We report the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 100 publications
(144 reference statements)
0
67
0
Order By: Relevance
“…The ability to tune the extent of emulsification with the choice of electrolyte provides a robust alternative to spontaneous emulsification methods via more complex strategies. Finally, our results offer insight into a new physical means by which nature can spontaneously produce microcompartments, a topic of intense interest in understanding the abiotic origins of life 27,[30][31][32] .…”
Section: Oilmentioning
confidence: 90%
“…The ability to tune the extent of emulsification with the choice of electrolyte provides a robust alternative to spontaneous emulsification methods via more complex strategies. Finally, our results offer insight into a new physical means by which nature can spontaneously produce microcompartments, a topic of intense interest in understanding the abiotic origins of life 27,[30][31][32] .…”
Section: Oilmentioning
confidence: 90%
“…This result suggests the survival of a significant fraction of the reactive carbocation in the DESI secondary microdroplets, despite a small fraction of the carbocation annihilation by the nucleophilic attack of water (H 2 O 18 ). This result is in line with the proposal that carbocations primarily span life at or near the air/water interface, which is effectively water-poor. …”
Section: Resultsmentioning
confidence: 99%
“…This is a very active area research as the enhancement of chemical reactions in aerosol particles contains many unknowns 319 and is believed to play an important role in prebiotic chemistry. [320][321][322] The study of chemical transformations using Raman scattering from optically trapped particles is limited to systems that contain only a few components; beyond this, the spectra become difficult to analyze. As discussed earlier, this is another area where EDBs have shown promise, as it has been demonstrated that they can be coupled with high performance mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%